1991
DOI: 10.1152/ajpgi.1991.261.5.g770
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between capsaicin-stimulated calcitonin gene-related peptide and somatostatin release in rat stomach

Abstract: Calcitonin gene-related peptide (CGRP) is present in the stomach, and exogenous CGRP stimulates gastric somatostatin release. A study was undertaken to elucidate the functional linkage between CGRP and somatostatin in the stomach. Newborn Wistar rats were made CGRP deficient by intraperitoneal injection of capsaicin 2 days after birth, and then 2.5 mo later, release of CGRP and somatostatin was examined by vascular perfusion of the isolated stomach. In CGRP-deficient rats, neither the content nor basal secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Potential mechanisms may involve capsaicin-sensitive afferents containing calcitonin gene-related peptide (CGRP) signaling known to be activated by abdominal surgery (29,46,75). There is also an established linkage between capsaicin-sensitive afferent stimulation containing CGRP and the increase in gastric somatostatin release (8,34,48). Collectively, these data support the contention that the reduction of circulating ghrelin levels in rats induced by peripheral administration of somatostatin (18,55,57) or sst 2 agonist (present study) and by endogenous somatostatin released by urethane or likely by abdominal surgery involves the activation of sst 2 receptors expressed on gastric X/A-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms may involve capsaicin-sensitive afferents containing calcitonin gene-related peptide (CGRP) signaling known to be activated by abdominal surgery (29,46,75). There is also an established linkage between capsaicin-sensitive afferent stimulation containing CGRP and the increase in gastric somatostatin release (8,34,48). Collectively, these data support the contention that the reduction of circulating ghrelin levels in rats induced by peripheral administration of somatostatin (18,55,57) or sst 2 agonist (present study) and by endogenous somatostatin released by urethane or likely by abdominal surgery involves the activation of sst 2 receptors expressed on gastric X/A-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism ofgastroprotection afforded by paren teral capsaicin has been little studied, but in case of aciddependent mucosal lesions (ASA or WRS) it could be attributed to the inhibition of gastric acid secretion possi bly mediated by locally released somatostatin [32], Fur thermore. parenteral capsaicin might stimulate the affer ent nerves and enhance the release of vasoactive neuro transmitters such as CGRP [33] which could be one of the candidates responsible for the hyperemia accompanying protection afforded by capsaicin.…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral action of capsaicin is a dose-dependent action (Szolcsányi 1984;Mózsik et al 2001) (Table 9.5). Capsaicin releases CGRP and SP (Inui et al 1991;Dömötör et al 2005), which modifies the vascular reactions in the gastrointestinal mucosa (Sipos et al 2006) recently demonstrated that the existence of neuroimmune link between the CGRP, SP, and immune cells in the gastric mucosa of patients with chronic gastritis. Dömötör et al (2006b) demonstrated the increased release of glucagon during a sugar loading test in healthy human subjects, indicated a new step of capsaicin-induced changes taking place between the capsaicin-sensitive afferent nerves and neurohormonal regulation.…”
Section: Capsaicin-sensitive Afferentation In Patients Withmentioning
confidence: 99%